Non-classical localization of androgen binding proteins in the C2C12 skeletal muscle cell line - Pronsato, Lucía (2013)
The classical model of testosterone action has been traditionally described as being mediated by the androgen receptor (AR) localized exclusively in the nucleus. However, there is increasing functional evidence for extranuclear localization of AR. We present biochemical and immunological data supporting mitochondrial and microsomal localization of AR in the C2C12 skeletal muscle cell line. As a first approach AR was detected by immunoblotting, using specific antibodies after subcellular fractionation, not only in nucleus and cytosol, but also in mitochondria and microsomes. We then established [3H] testosterone binding characteristics in total homogenates and subcellular fractions. Specific and saturable [3H] testosterone binding sites were detected in mitochondria and microsomes. Immunolocalization of the non-classical AR was also confirmed using confocal microscopy. Sucrose gradient fractionation demonstrated the presence of the AR in lipid rafts and caveolae. Besides, the AR interacts physically with Caveolin-1, association that is lost after testosterone treatment. Accordingly, Western blot analysis revealed a decrease of AR expression in the microsomal fraction after testosterone treatment, suggesting translocation of the membrane AR to another subcellular compartment. The non-classical distribution of native pools of AR in skeletal muscle cells suggests an alternative mode of AR localization/function.